2010
DOI: 10.1016/j.phrs.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

P2Y13 receptor is responsible for ADP-mediated degranulation in RBL-2H3 rat mast cells

Abstract: Extracellular ADP is known to play many important physiological roles. In this study, we identified the P2Y13 receptor in a rat mast cell line (RBL-2H3) and explored the functional role of ADP, its endogenous agonist. ADP induced both intracellular calcium mobilization and release of hexosaminidase (Hex). In an assay of intracellular calcium, ADP was 100-fold less potent than and equally efficacious as the P2Y1 receptor-selective agonist MRS2365. However, ADP was more potent and efficacious than MRS2365 in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Schulman et al confirmed the presence of P2Y 1 and P2Y 2 , but not P2X7 transcript in HLMC's as discussed above. Recent studies indicate that P2Y 13 and P2Y 14 might also be involved in mast cell degranulation, since these receptors induce β-hexosaminidase release in RBL-2H3 rat mast cells [215,221] while P2Y 14 was also reported to potentiate C3a-induced β-hexosaminidase release in human LAD2 cells [216] (Table 1). Triggering of intracellular Ca 2+ signaling in mast cells is also linked to cytokine expression and release.…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schulman et al confirmed the presence of P2Y 1 and P2Y 2 , but not P2X7 transcript in HLMC's as discussed above. Recent studies indicate that P2Y 13 and P2Y 14 might also be involved in mast cell degranulation, since these receptors induce β-hexosaminidase release in RBL-2H3 rat mast cells [215,221] while P2Y 14 was also reported to potentiate C3a-induced β-hexosaminidase release in human LAD2 cells [216] (Table 1). Triggering of intracellular Ca 2+ signaling in mast cells is also linked to cytokine expression and release.…”
Section: Mast Cellsmentioning
confidence: 99%
“…The P2Y 11 receptor could thus be a novel potential therapeutic target for the amelioration of neutrophilic inflammation in a wide range of inflammatory diseases [35]. Another possible mechanism of action that involves to the inhibition of P2Y 11 14 receptor-activation directly induces mast cell degranulation [215,221] while P2Y 14 receptors also potentiate C3a-induced degranulation [216]. DAMP damage-associated molecular patterns, PAMP pathogen-associated molecular patterns, C3a complement 3a, C3aR complement 3a receptor.…”
Section: Therapeutic Potential Of P2 Receptor Targetingmentioning
confidence: 99%
“…The ability of activation of certain receptors to enhance antigen-mediated degranulation led to the suggestion that under some conditions; these receptors have the capacity to contribute to allergic responses in vivo [1]. The class of receptors for extracellular nucleotides comprises eight GPCRs (P2Y 1,2,4,6,11,12,13,14 ) and seven LGICs (P2X 1-7 ), many of which being expressed in blood cells [6]. The roles of P2 receptors in mast cell biology have recently been reviewed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotides, especially adenosine 5′-diphosphate (ADP) and adenosine 5′-triphosphate (ATP), have been studied previously in the context of mast cell degranulation [9,10], but specific receptor subtypes mediating these functions have not been systematically explored. We recently demonstrated in RBL-2H3 basophillic cells, a degranulation model of rat mast cells, that P2Y 13 R and P2Y 14 R are involved in degranulation [11,12]. However, the role of various P2YRs in human mast cells has been largely unexplored, although isolated studies indicate the possible involvement of certain P2YRs [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…P2Y 13 is a GPCR activated by ADP and coupled to G i /G o signalling [10]. It was initially identified in the spleen and brain but is also expressed in the dorsal root ganglia, microglia, pancreatic beta cells, hepatocytes and mast cells [10][11][12][13][14][15]. In central neurons, P2Y 13 has been shown to be involved in neuronal differentiation, axonal elongation, oxidative stress and inflammatory pain behaviour [11,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%